CONDUCTING EXPERIMENTS WITH NEWLY DESIGNED SAW GIN RIBS IN THE COTTON CLEANING PROCESS FOR DIFFERENT COTTON VARIETIES - Kozokov, Saidmukhtar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Experiments were conducted to determine the effect of using newly designed convex-surfaced saw ribs in a cotton cleaning machine for removing large impurities, comparing their cleaning efficiency with that of standard ribs across different cotton varieties. The experiments also aimed to assess how much cotton fragments are lost to the impurity bunker when using convex-surfaced ribs compared to conventional ones. The results showed that the cleaning efficiency of convex-surfaced ribs is significantly higher.